Pengaruh Pengaruh Fasilitas Kamar Terhadap Kepuasan Tamu Menginap Di Hotel Pangeran Beach Padang - Miranti, Yolanda; Yuliana, Yuliana (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
Abstract This study began with observations during the pre-study of guests staying at the Prince Beach Hotel in Padang. It was found that there were problems with the needs of guests who were not properly met so that guests were dissatisfied, including those who complained about room facilities that were experiencing a lot of damage that were considered less provide comfort for guests. This study aims to analyze the effect of room facilities on guest satisfaction staying at the Prince Beach Hotel Padang. This type of research is classified as quantitative research with a causal associative approach. The study population was individual guests who stayed overnight with an average monthly rate of 1,707 people. The research sample of 95 using purposive sampling technique. Data collection is done by distributing questionnaires using a Likert scale that has been tested for validity and reliability. Data analysis using simple linear regression with SPSS version 16.00. The results showed that: room facilities were classified as good (73.7%), and guest satisfaction was classified as good (61.05%). R square values ​​were obtained (10.3%), and the significance was 0.002 <0.05. This means that the influence of room facilities on guest satisfaction by 10.3% while 89.7% is influenced by other factors. Keywords: Room Facilities, Guest Satisfaction